2002
DOI: 10.2134/jeq2002.1722
|View full text |Cite
|
Sign up to set email alerts
|

Solute Transport Modeling under Cultivated Sandy Soils and Transient Water Regime

Abstract: Drainable lysimeters offer the possibility to integrate heterogeneous solute leaching conditions caused by row crops and transient water regime, and to conveniently measure water and solute fluxes at the drainage outlet. To compare solute leaching behavior in and around drainable lysimeters operating under a transient water regime in potato (Solanum tuberosum L.) fields, parameters of the convective lognormal transfer (CLT) function model were fitted using bromide (Br-) flux concentrations (Cf) measured in lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…Site and instrumentation are described in detail in Gasser (2000) and Gasser et al (2002). Briefly, 15 drainable lysimeters (1 m 2 surface) were installed during July and August 1995, in five fields cultivated by potato farmers of the Portneuf region located near Quebec City, Canada.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Site and instrumentation are described in detail in Gasser (2000) and Gasser et al (2002). Briefly, 15 drainable lysimeters (1 m 2 surface) were installed during July and August 1995, in five fields cultivated by potato farmers of the Portneuf region located near Quebec City, Canada.…”
Section: Methodsmentioning
confidence: 99%
“…The soil physical and chemical properties measured at the beginning of the monitoring period (May 1996) were presented in detail in Gasser (2000) and Gasser et al (2002). Mean and standard deviation of selected soil properties for 15 lysimeter locations are reported in Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this method is very time-consuming and inefficient to determine drip fertigation scheduling for potato, because many multitreatment trials are needed for the different nutrient application levels: Nitrogen (N), phosphorus (P) and potassium (K) (Chawla and Narda, 2001;Darwish et al, 2006;Janat, 2007;Kaur et al, 2005;Kumar et al, 2007;Mohammad et al, 1999;Papadopoulos, 1988;Singh et al, 2004). Due to variations in water movement, spatial and temporal distribution within the soil and fertilizer application method, nutrient transport and distribution in the wetted soil volume under drip irrigation differ from those under conventional irrigation (flood, furrow and sprinkle) (Gasser et al, 2002). However, the fertilization requirement for potato is mainly determined by its biological characteristics.…”
Section: R E G U L a R A R T I C L Ementioning
confidence: 99%
“…For example, Vanderborght et al (1996) installed horizontal TDR probes at different depths in a lysimeter having a 1 m deep undisturbed layered sandy soil monolith and found that m I and s I in the surface layer (7.5 cm depth) were 2.80 and 1.01, respectively. Furthermore, Gasser et al (2002) conducted a leaching study in a potato field with sandy soil and determined transfer function parameters for Br resident concentrations in the soil profile of 105 cm around the lysimeter. They reported lower m I of 1.28 and larger s I of 1.07 at 7.5 cm observed depth.…”
Section: Near-surface Time Domain Reflectometry Measured Concentrationsmentioning
confidence: 99%